Researching of modulation of radiation intensity in multimode polymer fiber under selective excitation of modes - Варищук, Василь Ігорович; Татарин, Василь Ярославович; Бобицький, Ярослав Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
When coherent light is propagated into the multimode fiber, a speckle pattern is formed at the exit face of fiber.When the fiber is vibrated, the speckle pattern is modulated due to mode coupling and phase modulation of the propagating modes.In this paper the effect of fiber bends on theintensity modulation of the off-axis modes in multimode polymer fiber has been investigated. The theoretical analysis of a bend multimode fiber shows that the change of the speckle pattern intensity depends on the length of the fiber perturbed and amplitude of the vibration signal. When a highly coherent light source is used, the speckle pattern modulation is due primarily to phase modulation of the modes, and the component of the induced frequency overcomes the first and second harmonics with a difference of 13 dB and 18 dB, respectively, which allows clear identification of the induced vibration frequency. In contrast, when less coherent sources are used, the difference between fundamental vibration frequency and its harmonic components are small. Experimentally shown that when the off-axis modes are excited in multimode polymer fiber the amplitude of the output signal depends linearly on the amplitude of the vibration signal. The considered modulation mechanism can be effectively used to detection of the vibration and mechanical oscillation.